FLUKS GAS RUMAH KACA CO2, CH4 DAN N2O PADA LAHAN EKOSISTEM MANGROVE DI SUNGAI TALLO, MAKASSAR (Fluxes of greenhouse gases CO2, CH4 and N2O from mangrove soil in Tallo River, Makassar) - Rahman Rahman; Yusli Wardiatno; Fredinan Yulianda; Hefni Effendi; Iman Rusmana (Jurnal Biologi Tropis, 2018)
Studies on the fluxes of greenhouse gases in mangrove ecosystems especially during tides are relatively scarce. The research was conducted in Tallo River Makassar which is a mangrove ecosystem habitat. Gas sampling was done by utilising size 0,5x0,5x1 m3 chamber through a syringe during the tidal periods. Gas analysis was done using gas chromatography methods. The research shows that the flux of CO2 gasduring high tide was 204,84 mg m-2 hr-1 or 1,79 kg m-2 year-1 ÃÂ and 183,81 mg m-2 hr-1 or 1,61 kg m-2 year-1 during low tide, while the flux of CH4 gaswas 0,75 mg m-2 hr-1 or 0,007 kg m-2 year-1 ÃÂ during high tide and 0,62 mg m-2 hr-1 or 0,005 kg m-2 year-1 during low tide, and the flux of N2O gaswas 0,141 mg m-2 hr-1 or 0,0012 kg m-2 year-1 ÃÂ during high tide and 0,145 mg m-2 hr-1 or 0,0013 kg m-2 year-1 ÃÂ during low tide. Keywords : greenhouse gas flux, mangrove ecosystem, Tallo River